Pengaruh Other Comprehensive Income, Kompleksitas Perusahaan Dan Ukuran KAP Terhadap External Audit Fee Pada Perusahaan Yang Terdaftar Di Indeks Saham Syariah Indonesia (ISSI) Tahun 2020-2023 - Novi Mubyarto; Faturahman Faturahman; Dyah Wulandari (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2025)
This study aims to determine and analyze the effect of other comprehensive income, company complexity and public accounting firm size on external audit fees for companies listed on the Indonesia Sharia Stock Index 2020 - 2023. The sample used was 23 companies listed on the Indonesian Sharia Stock Index consistently from 2020 to 2023. The method used is a quantitative method using secondary data processed with the help of the EView 12 application. The results of the partial test analysis show that other comprehensive income and company complexity have no significant effect on external audit fees. Meanwhile, public accounting firm size has a significant positive effect on external audit fees due to the better audit quality of Big Four public accounting firm. In addition, there is an effect of other comprehensive income, company complexity and public accounting firm size simultaneously on external audit fees. Although public accounting firm size contributes individually, the combination of the three variables has a significant influence on the determination of external audit fees that must be paid by the company.